The challenge of managing tendinopathy in competing athletes. Issue 7 (10th May 2013) - Cook, J L; Purdam, C R
Abstract : Managing tendinopathy in season is a challenge for all sports medicine practitioners. Many of the strategies employed to treat tendinopathy in a rehabilitation setting are not suitable because of the time taken to recover. Management strategies that control pain and maintain performance are required. These include load management, both reducing aggravating loads and introducing pain-relieving loads, medications and adequate monitoring to detect a deteriorating tendon. Other interventions such as intratendinous injection therapies and other direct tendon modalities can be provocative at worst and without effect at best. Research to improve the understanding of management in athletes in season is compromised by ethical considerations and access to willing participants. It is likely to remain an area where clinical advances guide future treatments.